Internalizing the Value of Patience through Islamic Education Based on the Tablighi Jamaat Movement - Raden Sumiadi (Jurnal Ilmiah Mandala Education (JIME), 2026)
This research examines the role of Islamic education based on the Jamaah Tabligh movement in shaping the character of patience among its followers. Patience is one of the fundamental values in Islam that plays a crucial role in shaping a resilient Muslim personality capable of facing various life challenges. Jamaah Tabligh, as a global Islamic missionary movement, has a distinctive educational method that emphasizes direct practice through the khuruj (going out for missionary work) program. This research aims to analyze the concept of patience character education from the perspective of Islamic education, identify the educational model applied by Jamaah Tabligh, and evaluate the effectiveness of this method in shaping the character of patience. The approach used is qualitative with a descriptive-analytical method, collecting data through observation, interviews with followers, and document studies. The results show that Jamaah Tabligh implements patience character education through several main strategies: regular worship during khuruj, learning to obey decisions resulting from consultations, learning the stories of the prophets and companions, direct experience in challenging missionary work, and a continuous mentoring system. The khuruj program serves as a practical laboratory that trains patience in facing rejection, material limitations, and adaptation to new environments. The internalization of the value of patience is manifested through dhikr (remembrance of God), mudzakarah (discussion), obedience to the results of consultations, and the exemplary behavior of the followers. This research concludes that Islamic education based on the Jamaah Tabligh movement has been effective in shaping the character of patience through a holistic approach that integrates spiritual, emotional, and social aspects, emphasizing experiential learning and continuous guidance within a supportive community.